Application of seismic resisting systems for building construction in Malaysia - Hamid N.B.; Razak S.N.B.A.; Sanik M.E.; Mokhtar M.; Sahat S.; Kaamin M.; Ramli M.Z. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Over the centuries, there has been a lot of earthquakes occur due to sudden changes in the surface of the earth. This phenomenon has caused property destruction, a large number of deaths and damage to buildings. This situation has become a concern by experts, especially engineers around the world since the damage of the building caused huge losses as well as contributing to the loss of life due to burial and so forth. Therefore, this study is conducted to compare the changes of node displacement that occur in each designed buildings caused by the seismic load applied and to determine the best design system that has the smallest amount of node displacement changes during the quake. In this study, three types of model that consist of base frame, shear wall and braced frame are designed using STAAD Pro Software to obtain their displacement reading. Important data such as seismic parameters and load cases which is Zone factor: 0.24, Response reduction factor: 5, Importance factor: 1.5, Structure type: Concrete, Damping: 0.05, Foundation soil type: Medium, Dead load intensity at all floor levels: 6kN/m2, Live load for roof: 1.5kN/m2 and Live load for other floors: 3kN/m2 are inserted. The strength of resistance toward seismic load between the three models can be evaluated through the displacement occurs in the nodes in every model. BEIESP.